Pengesahan Nikah pada Pasangan di Bawah Umur - Muhammad Nafi (Jurnal Humaya: Jurnal Hukum, Humaniora, Masyarakat, dan Budaya, 2023)
This article discusses the legal considerations of judges in adjudicating marriage certificate cases filed when the parties are minors. The legal problem is that the endorsement of an underage marriage is considered a violation of the law. This research is empirical or sociological legal research of a descriptive nature. Primary and secondary data types that include primary, secondary, and tertiary legal materials. The data collection techniques used are field studies and literature studies, then technical analysis used is qualitative methods with interactive analysis models. Data collection is carried out by documentation techniques, and literature studies. The results of this study showed that the Explanation of the Clerk of the Supreme Court Number 231/PAN/Hk.05/1/2019, answered the letter from the Director General of The Directorate General of Religious Affairs Number 472.2/18752/DUKCAPIL, which explained that the application for marriage certificate submitted by an underage couple must be rejected by the Religious Court, because it is considered a form of violation of the law.  But in its implementation the judge looked at the conditions of the maslahat that were dug out of the examination at the trial.